Patriarchal trauma and (the limits of) psychoanalysis across time, place and race : female suffering in Washington Square, Wide Sargasso Sea and The joys of motherhood : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts, School of Humanities, Media and Creative Communication, Massey University, New Zealand - Gonouya, Caroline (Massey University, 2022)
If, as is widely claimed, literature reflects social norms, cultural values, class struggles and 'social facts' about, and (scientific) knowledge available at the time in which it was written, Shoshana Felman’s claim in Writing and Madness also seems valid: "Historically, literary knowledge mirrors psychiatric knowledge and in many ways competes with it" (3). This provides a frame for my discussion of three novels in this thesis: Henry James's Washington Square, Jean Rhys's Wide Sargasso Sea, and Buchi Emecheta's The Joys of Motherhood. These novels, written by authors living in very different times and places, all portray the suffering of women as a result of patriarchal trauma in three distinct historical and geographical settings: early Victorian New York, early Victorian West Indies and colonial Nigeria, respectively. These texts all reflect socio-cultural practices that subordinated women (at the time of writing and/or the time in which they are set), and all "mirror" or "compete with" psychological and psychiatric knowledge dominant at the time of writing. They are linked by a common thread of trauma that affects the mental well-being of the female protagonist(s), whether this be depression, suicidal ideation or 'hysteria.' I argue that in each of the three texts I discuss, we can find clues about the author's intellectual and cultural milieu – dominant ideas that were being discussed and debated at the time – and this can tell us something about developments in psychology and psychoanalysis in the (almost) century traversed by their publication dates. It is my claim that the scientific discoveries and psychological theories of the time in which the authors wrote similarly left their mark on the novels and the ways in which the (female) protagonists are portrayed. My discussions of the novels thus traverse patriarchal Darwinism and its influence on the nascent 'science' of psychology and Freudian psycho-sexual theories of development; it also considers the challenges to these scientific and medical forms of knowing (women) raised by second-wave feminism and object relations theory, and African womanism. I discuss how these novels reflect changing understandings of trauma, patriarchy and womanhood and the relationship between them; I also argue that they are open to reinterpretation via developments in trauma theory over the past century, as the reader views them through differing 'apertures' (in James's term): from theories of female 'hysteria' to broader understandings of intergenerational and postcolonial trauma.
Keywords: 470526 Other literatures in English